2002
DOI: 10.1093/brain/awf110
|View full text |Cite
|
Sign up to set email alerts
|

The minicolumn hypothesis in neuroscience

Abstract: The minicolumn is a continuing source of research and debate more than half a century after it was identified as a component of brain organization. The minicolumn is a sophisticated local network that contains within it the elements for redundancy and plasticity. Although it is sometimes compared to subcortical nuclei, the design of the minicolumn is a distinctive form of module that has evolved specifically in the neocortex. It unites the horizontal and vertical components of cortex within the same cortical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
343
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(360 citation statements)
references
References 147 publications
16
343
0
1
Order By: Relevance
“…These experimental findings strongly supported that the cortical columns are basic anatomical and physiological units of the cortex and suggested that columns might be of fundamental importance for the function of the brain [2,3] .…”
supporting
confidence: 57%
See 1 more Smart Citation
“…These experimental findings strongly supported that the cortical columns are basic anatomical and physiological units of the cortex and suggested that columns might be of fundamental importance for the function of the brain [2,3] .…”
supporting
confidence: 57%
“…Since it was first reported in 1957 [1] , the columnar organization has been found in somatic sensory cortex, visual cortex, auditory cortex, motor cortex and association cortex of various different species including mice, rat, cats, rabbits, monkeys and humans [2] . These experimental findings strongly supported that the cortical columns are basic anatomical and physiological units of the cortex and suggested that columns might be of fundamental importance for the function of the brain [2,3] .…”
Section: Doi: 101360/03yc0240mentioning
confidence: 99%
“…It is an anatomically (spatially) distinct circuit of about one or two hundred neurons, oriented perpendicularly to the surface of the cortex (Fig. 3), within which the autonomy of individual neurons is reduced [163] due to dense intrinsic connectivity [164][165][166]. It is supposed that minicolumns possess relatively stereotypic internal processing, and maintain generic patterns of inputs and outputs with minicolumns in other regions [167,168].…”
Section: Spatial Structure Of Neuronal Assembliesmentioning
confidence: 99%
“…The minicolumn hypothesis of Buxhoeveden et al (Buxhoeveden and Casanova 2002a), or a size-scaled version of that concept has been used to come up with a spatially repeating local circuit, which is then used as a skeleton to fashion together longer range connections. The total number of neurons per minicolumn (16 neurons) as well as the size scale is similar to that found by Buldyrev et al (Buldyrev et al 2000) and Buxhoeveden and Casanova (Buxhoeveden and Casanova 2002b).…”
Section: Introductionmentioning
confidence: 99%